Hormonal induction of oestrus in anoestrous buffaloes - PANT, H C; BAROT, L R; DUGWEKAR, Y G; KASIRAJ, R; PRABHAKAR, J H (The Indian Journal of Animal Reproduction, 2023)
The efficacy of a 9 day progestagen treatment in combination with eCG was evaluated for induction ofovulatory oestrous, restoration of ovarian cyclicity and fertility in rural anoestrous buffaloes maintained eitheron paddy straw plus dried jowar (group I) or with urea molasses mineral mixture block (UMMB) supplement· (group IT) during their non-breeding season (summer). Honnonal therapy was quite effective in the induction ofoestrus but the conception rate at the induced.oestrus was vecy poor (8.3% vs 13 .5%). The UMMB supplementimproved the energy balance of animals (serum glucose value; 24.8 vs 50.3 mg%) and consequently theincidence of ovulatory oestrus (16. 7 vs 53.3%) and the establishment of ovarian cyclicity (25.0 vs 60.0%).Further studies are needed to delineate the role of nutrition and its interaction with season in assessing theresponse to honnonal therapy for treatment of true anoestrus in rural buffaloes
Keywords: Anoestrous; buffalo; hormonal therapy; serum glucose; progesterone; fertility